Use of post flame metal-based and oxygenated additive combination for biodiesel-diesel blends - Husnawan, M.; Masjuki, Haji Hassan; Mahlia, T.M.I.; Mekhilef, Saad; Saifullah, M.G. (2009)
This paper presents effects of using vegetable oil-based additive combined with metal-based additive on exhaust emissions of 4-stroke diesel engine fueled with biodiesel. Tests were conducted using biodiesel from palm blended with diesel, palm polyol and MgO as a post-flame additive. A test with 100 conventional diesel fuel was also conducted for comparison purposes. PaImbiodiesel blended fuel with and without additive generally produced less emission compared to ordinary diesel. Moreover, post flame additives was found successfully diminishing poisonous exhaust gases from diesel engine combustion, eliminating stringent environmental issues on atmospheric pollution.